Microwave drying behaviour of apple slices. (November 2013) - Çelen, Soner; Kahveci, Kamil
In this study, microwave drying behaviour of apple slices was investigated experimentally to determine the effect of microwave power on drying, energy consumption and colour quality. Microwave drying behaviour was simulated by a theoretical drying model. Suitability of several empirical and semi-empirical models in defining the microwave drying behaviour of apple slices was determined by statistical analysis. The experimental results show that the drying time, energy consumption and the colour quality of apple slices decrease considerably with an increase of microwave power. The modelling results indicate that theoretical model simulates microwave drying behaviour of apple slices very well and among the empirical and semi-empirical models, the Page model yields the best fit with the experimental data. The modelling results also show that the excess pressure inside the apple slices shows first an increasing trend and then begins to decrease as the moisture content takes lower values.